Cosmopolitan Education in Agonistic Morality: Epistemological Restraint, Discourse Ethics, and Agonistic Pluralism - Hayden, Matthew J. (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2018)
Cosmopolitan education has been much theorized, discussed, and proposed, but what, exactly, might it look like and what specific processes might it involve? Cosmopolitanism’s recognition of shared humanity and the subsequent entailment of democratic inclusion make explicit the moral and political nature of cosmopolitan education and philosophy. As an ethico-political process, existing political and ethical processes can be brought to bear on its educational manifestations. The political concepts of epistemological restraint, discourse ethics, and agonistic pluralism are offered as models for cosmopolitan education in agonistic morality: epistemological restraint is used to address the need for prioritization of moral inquiry over moral belief; discourse ethics addresses the necessity of inclusive and democratic dialogue; agonistic pluralism offsets the implications of the inevitability of pluralism in educational inquiry. All three combine to form a process of cosmopolitan education in agonistic morality.